IMPLEMENTATION OF PERSONNEL POLICY BY MILITARY ADMINISTRATIONS UNDER CONDITIONS OF MARTIAL LAW - Shapenko, Lyudmila; Liadnov, Anton; Liadnov, Olexandra (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to justify the objective necessity and special aspects of modernizing the provision of personnel, as well as to form proposals for improving the administrative and legal regulation of the personnel provision process in military administrations as a key element of the functioning of the institution, the main tasks of which include implementing measures of the legal regime of martial law, defense, civil protection, public safety and order, protection of rights, freedoms, and legitimate interests of citizens. Research methods: the methodological basis of the research consisted of general scientific and special legal methods of cognition, in particular dialectical and system-functional methods, which allowed analyzing the priority directions of modernization of public-legal relations in Ukraine, primarily in terms of improving the provision of personnel in military administrations. The result of the proposed scientific work is the development of theoretical provisions, based on which it is determined that at the present stage of building the Ukrainian state, the priority direction for conducting innovative modernization of public-legal relations in Ukraine in the context of building a strategy during the war is the creation of a transparent system of the provision of personnel in military administrations, improving the level of efficiency and effectiveness of their activities. Since one of the key aspects for the development of military administration is the provision of personnel, the achievement of tasks set before military administrations depends on the appropriate qualification of their personnel, discipline, teamwork, and ability for professional growth. Discussion: qualitative changes in the process of public administration reform can only be achieved by implementing innovative activity methods. After all, the sphere of public administration must respond to today's transformations, overcoming technological underdevelopment through systematic implementation of innovations in the activities of public administration bodies.